2000
DOI: 10.1007/pl00012919
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity, Mating Ability and DNA Restriction Fragment Length Polymorphisms of Pyricularia Populations Isolated from Gramineae, Bambusideae and Zingiberaceae Plants

Abstract: Eighty-five Pyricularia isolates were collected from 29 host species of Gramineae, Bambusideae and Zingiberaceae plants sampled in Brazil, Uganda, Ivory Coast, India, Nepal, China, Indonesia and Japan. These isolates were compared on the basis of pathogenicity, mating ability and restriction fragment length polymorphisms with single-copy DNA probes. Based on the pathogenicity to eight differential gramineous plants, these isolates were classified into seven pathotypes : finger millet type, foxtail millet type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
181
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(193 citation statements)
references
References 26 publications
5
181
0
2
Order By: Relevance
“…AFLP marker was also recognized here to be the most useful DNA fingerprinting tool for resolving the high genetic variation of this fungus compared with other fingerprinting techniques applied by several previous researchers such as RAPD and rep-PCR (6,15,(22)(23)(24). However, this research confirmed results obtained by JavanNikkhah (15) showing the low genetic variation among strains isolated from rice in Iran.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…AFLP marker was also recognized here to be the most useful DNA fingerprinting tool for resolving the high genetic variation of this fungus compared with other fingerprinting techniques applied by several previous researchers such as RAPD and rep-PCR (6,15,(22)(23)(24). However, this research confirmed results obtained by JavanNikkhah (15) showing the low genetic variation among strains isolated from rice in Iran.…”
Section: Discussionsupporting
confidence: 81%
“…The low level of pathotype diversity (22) and lack of correlation between DNA fingerprint and pathotypes suggest that selection has favored the same spectrum of virulence in each clonal lineage. There was no evidence for sexual recombination in the studied population which is consistent with the dominant asexual reproduction observed in most rice-growing areas of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Magnaporthe oryzae (Ascomycotina) infection causes severe diseases in rice that affects yield, and can also infect many other gramineous plants (Kato et al, 2000;Couch and Kohn, 2002). Rice varieties that contain resistance genes can easily lose their resistance after years of consecutive large-scale cultivating, because the resistance is quickly circumvented by the emergence of virulent strains, which are caused by deletion of the Avr gene (Yoshida et al, 2009), expression modification (Kang et al, 2001;Fudal et al, 2007) and point mutation (Orbach et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several genes involved in cytosine methylation have been identified in these organisms. Dim-2 in N. crassa (Kouzminova and Selker 2001) (Kato et al 2000; Couch and Kohn 2002). Interestingly, we previously found that the DNA methylation status of the long terminal repeat (LTR) retrotransposon, Magnaporthe gypsy-like element (MAGGY), differed among the M. oryzae subgroups.…”
mentioning
confidence: 99%
“…Taxonomically, it belongs to the class Ascomycetes and family Sordariaceae, as does N. crassa. Magnaporthe isolates can be classified into several subgroups according to their host plants (Kato et al 2000;Couch and Kohn 2002). Interestingly, we previously found that the DNA methylation status of the long terminal repeat (LTR) retrotransposon, Magnaporthe gypsy-like element (MAGGY), differed among the M. oryzae subgroups.…”
mentioning
confidence: 99%